HUBUNGAN JUMLAH SEL NEUTROFIL DENGAN KADAR TROPONIN I PADA PENDERITA INFARK MIOKARD AKUT - Hikma , Candra Triana; Anik, Handayati; Sri Sulami , Endah Astuti (Politeknik Kesehatan Kementerian Kesehatan Surabaya, 2021)
Acute Myocardial Infarction (AMI) is a heart disease condition due to heart muscle cells not getting enough blood flow and oxygen due to atherosclerosis of the coronary arteries. When the condition of atherosclerosis gets worse, it will cause an inflammatory reaction, causing an increase in neutrophils. Inflammation due to atherosclerosis will worsen blood flow to the heart, resulting in heart muscle necrosis which causes an increase in biochemical markers, namely cardiac troponin. The aim of this research is to determine the relationship between the number of neutrophil cells and troponin I levels in patients with Acute Myocardial Infarction.This type of research is a cross-sectional analytic observational with a retrospective approach. This research was conducted on patients with Acute Myocardial Infarction at the RSPAL dr. Ramelan Surabaya who performed a complete blood count and troponin I level with a period of January 1st 2020 – May 3rd 2021, taken by purposive sampling. The results showed that male respondents were 29 patients (63%) while female respondents were 17 patients (37%). Respondents aged 65 years amounted to 28 (61%) people, while respondents aged 65 years were 18 (39%) people. The results of the hypothesis test have a sig value of 0.000 < (0.05), so there is a relationship between the number of Neutrophil cells and Troponin I level in patients with Acute Myocardial Infarction. In hypothesis testing, the correlation coefficient value is 0.594, which means that there is a moderate relationship with a positive direction.